How big is home advantage at the Olympic Games? - Singleton, C.; Reade, J. J.; Rewilak, J.; Schreyer, D. (Discussion Paper 2021-13, 2021)
We revisit the magnitude of home advantage at the Summer and Winter Olympic Games, looking back all the way to Athens in 1896. By comparing a host country's success with their performances in previous and subsequent games, we find that home advantage has declined over time as participation and the diversity of competition have increased. Hosts of the Summer Olympics between 1988 and 2016 enjoyed a two-percentage-point boost in their shares of medals and finalists, compared with their performances overseas, in both men's and women's events. In this same contemporary period, the home advantage effect at the Winter Olympics was around fifty percent larger in men's events but non-existent in women's events. We also find evidence of significant performance spill overs on the previous and next Olympiads for countries when they hosted the Summer Games.